(untitled) (Journal of the College of Education for Women, 2019)
Trading global discourse topic as one of the other entrances to world peace, and the most important reasons for co-existence of intellectual and lumpy, and there Important issue related to a fundamental issue of the other cases are denied and the exclusion of others, Trading global discourse topic as one of the other entrances to world peace, and the most important reasons for co-existence of intellectual and lumpy, and there Important issue related to a fundamental issue of the other cases are denied and the exclusion of others, The stories of the prophets and their people the position of calling them and thought the new Massadik it. have found through research that there are two types of methods in the exclusion are as follows: First: mechanisms and practices directly affect the holders thought the offender, including: 1- murder and eradication existential.2-prison. 3- exile from home,and directing it. 4- social exclusion. Second:mechanisms and practices indirectly,include: 1- distortion of thought the other. 2- concealment of thought. 3–Denialofhearing thethought. 4–thebashing ofa pregnantthoughtthe other,in order toremove himand suppression.